PSYCHOSOMATIC ASPECTS IN THE TREATMENT OF GASTROESOPHAGEAL REFLUX DISEASE - V. I. Trofimov; Yu. N. Bezrukov (Архивъ внутренней медицины)
Gastroesophageal reflux disease is the most common disease of the esophagus, through the development of which is impaired motor function of the upper gastrointestinal system, allowing the disease to be quite be classified as psychosomatic, especially in the early stages of development, when no apparent organic complications that affect the structure of tissues. A significant percentage of mental disorders is observed in patients even before the development of somatic complaints. Patients in number of 105 people are examined. The first group — experienced (71 patient) received complex treatment, which includes the basic pathogenetic, symptomatic, and psychotropic treatment in the form of anxiolytics and antidepressants. The choice of drug was based on the results of psychological testing. The second group — the comparison group (34 patients) received only conventional treatment, without psychiatric support. Analysis was conducted of the astheno-vegetative syndrome, psychological characteristics of patients in relation to their disease, indicators of anxiety level and severity of depression. Patients with not erosive reflux disease have a frequency of detection of a depression and uneasiness was more than twice higher, than at patients with erosive reflux disease. After carrying out psychotropic treatment these indicators were practically made even. Prescription of psychotropic therapy in the form of antidepressants and anxiolytics has allowed to minimize the timing regression of clinical and psychosomatic manifestations of disease.